Characteristics of porous spherical LaFeO3 as ammonia gas sensing material. Issue 5 (22nd October 2021) - Nga, Phan Thi To; My, Dinh Thi Tra; Duc, Nguyen Minh; Kien, Pham Trung; Nhan, Phan Chi; Tu, Nguyen Cong; Huyen, Pham Thanh
Abstract: Porous spherical LaFeO3 (PS‐LFO) sample was prepared using a simple hydrothermal method and found to be a potential gas sensor for NH3 detection. Structural characteristic of the sample was examined by several techniques, including X‐ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRD investigation confirmed the formation of porous spherical LaFeO3 with a perovskite phase. TEM and SEM results revealed the porous structure of the material. The presence of functional groups was confirmed using Fourier transform infrared spectroscopy (FT‐IR). Orthorhombic porous spherical LaFeO3 calcined at 700 o C was employed as a gas sensor for detection of ammonia gas. The results revealed that PS‐LFO‐based sensor showed p ‐type gas sensing behavior with good sensitivity, rapid response, and sub‐ppm detection limit to ammonia gas at 325 o C.